Is there a need to review the syndromic case management of vaginal discharge due to candida in the Indian scenario? - Gedam, Swati T.; Waikar, Manjushri M.; Deogade, Kalindi S.; Sharma, Manisha K.; Gosavi, Sonali S.; Agarwal, Vandana A. (International Journal of Research in Medical Sciences, 2023)
Background: Vulvovaginal candidiasis (VVC) affects approximately 75% of women once in lifetime. National AIDS Control Organization has recommended Kit-2/Green (tablet secnidazole 2 gm OD stat and capsule fluconazole 150 mg OD stat) for syndromic case management (SCM) of patients with vaginal discharge since 2007. Patients are frequently revisiting the STI centre with recurrent VVC. The purpose of the study was to determine the effectiveness of fluconazole and other azoles in vulvovaginitis. Methods: Vaginal swabs from 188 patients attending regional STI centre, at Government Medical College, Nagpur between October 2020 to June 2022 were processed. A total of 128 conventionally confirmed isolates of Candida species were tested on RPMI 1640 medium for susceptibility to azoles by E test. An MIC of ≥8 μg/ml for fluconazole and ≥1 μg/ml for itraconazole, ketoconazole and voriconazole was interpreted as resistance as per CLSI M-60. Results: Candida species isolated were Candida albicans, C. glabrata, C. tropicalis, C. parapsilosis, C. dubliniensis and C. krusei. Candida species resistant to fluconazole, itraconazole, ketoconazole and voriconazole were 22 (17.18%), 53 (41.40%), 19 (14.84%), and 3 (2.34%) respectively. C. glabrata was most resistant while C. parapsilosis was least resistant. Voriconazole was most effective. Conclusions: Extensive use of fluconazole in syndromic case management of vaginal discharge could be the probable reason for 17.18% resistance to fluconazole. Withdrawal of fluconazole and replacement with another antifungal azole in SCM of vaginal discharge may prevent recurrent VVC and perhaps lead to emergence of fluconazole sensitive candida.